Exploration of Nurse Experiences in Providing Health Education in An Effort to Improve Activity of Daily Living (ADL) for the Elderly - Evianti Ensi Sele; Maria Syelvrida Tumina; Daeng Agus Vieya Putri Bhwa (Indonesian Journal of Global Health Research, 2026)
The elderly are a vulnerable age group that experiences a decrease in physical, psychological, and social functions, which has an impact on the ability to carry out daily activities (Activity of Daily Living) so that the elderly need the help of others in fulfilling their daily needs. Nurses have an important role in providing health education to improve the independence of the elderly, especially in primary care areas such as the Oekabiti Health Center. This study aims to explore nurses experiences on improving the Activity Daily Living of elderly. This study used a qualitative approach with a phenomenological method. Participants were collected by purposive sampling. Data were collected through in-depth interviews with 7 nurses who have more than 6 months of experience and are active in providing health education to the elderly. Data analysis was carried out with a thematic approach. This study resulted in five main themes, namely: (1) Nurses have a good understanding of health education; (2) health education is needed to improve the ADL of the elderly, (3) strategies for providing health education for the elderly, (4) challenges in providing health education for the elderly, (5) unavailability of health education media. This study shows that nurses have a good understanding of the importance of health education to improve the ADL skills of the elderly. Educational strategies are carried out personally and contextually, although they still face obstacles such as low health literacy and lack of educational media. Institutional support and media provision are needed to optimize elderly education.